Fundamentals of feminist gerontology - Garner, J. Dianne (Haworth Press, 1999)
"... co-published simultaneously as Journal of women & aging, volume 11, numbers 2/3, 1999."; Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)